THE PROFESSIONAL COMPETENCES: A LOOK ON THE INITIAL FORMATION IN THE PHYSICAL EDUCATION. (Fiep Bulletin - online, 2014)
The objective of this work was to reflect the formation of Physical Education teachers on its historical trajectory under the changing perceptions that happened during the formation of physical education professionals course (recent denomination). Therefore, it takes place, once more, in front of the challenge of the XXI century, in which changes are demanded by the market, quality is expected, and personal goals are requested. For the professionals that are graduated, they cannot deny that they generate philosophical, pedagogical, technological and economical changes, and they can, at any time, make their professionalism obsolete, and their only weapon would be their adaptation capacity, i.e. their re-qualification. A concern on the existential enrichment by offering opportunities of a decent professional performance is mandatory. The complexity of professional performances spots can be emphasized the school (different levels); leisure (many ways); recreation; dance (the most different ones); sports (countless); martial arts (very special), individuals with special needs (another actuation world); aesthetics, personal training, gym, events, and so many more, made by the diversity of schools of thoughts (many conceptions); it's not always offered, but it is always demanded by the students, clients, athletes, sportsmen and people from the most different areas, competence, knowledge, positive interaction, finally a worthy professional performance. Only the initial formation course, by the most different demandings, are not going to handle that the future professional are going to have the skills, the competences, the habits and the ethics for the profession performance. Like this, we are again on a crossroad: at on side, the market; and on the other, the professional-citizen. As much as the man, the professional of the future is showing its outlines, for their formation and performance agrees with mankind rules.
Keywords: formation of teachers; Physical Education; Performance training